Factors Associated with Antenatal Care Visit Dropout among Mothers attending Immunization Clinic - Subedi, Sabitra; Mandal, Punam K; Mahato, Anju K; Basnet, Bidhya; Rai, Munawatee; Khadgi, Deepika (Journal of Institute of Medicine Nepal, 2023)
Introduction Developing nations continue to have high maternal mortality rates. Prenatal care helps to improve the mother's and the unborn child's health. The purpose of this study is to identify the variables linked to mothers' antenatal care visit Drop out. The purpose of this study was to identify the variables linked to mothers' antenatal care visit droput. Method A cross-sectional study was carried out using the multi-stage sampling technique in the four urban and four rural randomly chosen municipalities of Morang district. In total, 134 postnatal mothers who skipped four focused ANC visits were chosen as cases at a ratio of 1:2, and 266 postnatal mothers who completed four focused ANC visit from the same vaccination facilities were chosen as controls. Using a semi-structured questionnaire and the consecutive sampling approach, data were gathered through interviews. The final model was chosen by employing the backward elimination technique after doing bivariate and multivariate analysis. Results This study found that the majority (56.0%) of cases was from the age group of 21-30 years and 35.1% of cases were janajatis. The number of factors were linked to ANC dropout, including age (OR 2.49, 95% CI 1.07-5.82), ethnicity (OR 2.29, 95% CI 1.05-4.99), education (OR 4.64, 95% CI 1.99- 10.81), income (OR 3.49, 95% CI 1.75- 6.95), and the existence of complications (OR 1.15, 95% CI 0.54-2.44). Conclusion The risk factors for ANC dropout were age, ethnicity, education, income, and the presence of complications during previous pregnancy. It suggests that efforts should be made to spread the information about the value of four focused ANC visits.